A Cu2O-TiO2 nanotube core-sheath structure and preparation method thereof
The preparation of Cu2O-TiO2 nanodivision sheath structure through electrochemical technology solved the problem of Cu2O loading to the inside of TiO2 nanotubes, achieving highly controllable filling rate and adaptability to industrial production.
Patent Information
- Application Number
- CN202211102888.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-09-09
AI Technical Summary
The prior art is difficult to achieve Cu2O payload into the TiO2 nanotube, and the filling rate is uncontrollable, and the preparation method is complex and not suitable for industrial production.
TiO2 nanotubes were prepared by electrochemical anodization and heat treatment annealing, and the conductivity of TiO2 nanotubes was improved by electrochemical cathode reduction technology, and Cu2O was loaded to the inside of TiO2 nanotubes through electrochemical pulse deposition technology.
It realizes efficient filling of Cu2O into the TiO2 nanotube, with a highly controllable filling rate, and a simple and low-cost method, which is suitable for industrial production.
Smart Images

Figure CN115386941B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nanocomposite materials, and in particular to a Cu2O-TiO2 nanotube core-sheath structure and a preparation method thereof. Background Art
[0002] Titanium alloys are ideal materials for shipbuilding and marine engineering due to their low specific gravity, high strength and excellent corrosion resistance. However, the biological inertness of titanium alloys makes them face serious biofouling problems. Among the many antifouling methods, loading the broad-spectrum biocide Cu2O onto the surface of titanium alloys is an effective way to achieve long-term antifouling performance. TiO2 nanotubes have a hollow structure, large specific surface area, highly controllable structure and strong direct bonding with the matrix, making them ideal nanocontainers for loading Cu2O onto the surface of titanium alloys.
[0003] At present, research on the preparation of Cu2O loaded to TiO2 nanotubes has been carried out at home and abroad. For example, the "Method of Cu2O nanoparticle sensitization TiO2 nanotube array photoelectrode" disclosed in the patent document of publication number CN105040062A loads Cu2O to the mouth of TiO2 nanotubes through electrochemical anodization and electrochemical pulse deposition technology. For example, the "Nano-heterojunction composite photocatalytic material based on TiO2 and its preparation" disclosed in the patent document of publication number CN106582641A proposes to use copper-titanium alloy to prepare TiO2 nanotubes and then perform heat treatment annealing to form Cu2O particles. And the "Preparation method of a Cu2O nanoparticle / TiO2 nanotube array composite heterojunction film" disclosed in the patent document of publication number CN108179455A proposes to first immerse TiO2 nanotubes in a copper acetate precursor solution, and then obtain granular Cu2O-modified TiO2 nanotubes by thermal decomposition. The review article "Hydrogen production through photoreforming processes overCu2O / TiO2composite materials: A mini-review" in the foreign journal "International Journal of Hydrogen Energy" looks forward to the research progress of Cu2O-TiO2 nanotube composites.
[0004] Although many scholars have used impregnation calcination method, multi-step chemical bath method, chemical reduction method and electrochemical deposition method to prepare Cu2O-TiO2 nanotube composite core-sheath structure, none of them can achieve the goal of complete filling and highly controllable filling rate.
[0005] At present, the following problems exist in the process of loading Cu2O into TiO2 nanotubes for antifouling: first, a large amount of Cu2O cannot be effectively loaded into the interior of TiO2 nanotubes, but forms Cu2O clusters on the top of TiO2 nanotubes; second, the amount of Cu2O loaded into TiO2 nanotubes is uncontrollable, and only small Cu2O particles can be loaded; third, the methods of loading Cu2O into TiO2 nanotubes are too complicated, such as hydrothermal method, template method and chemical reduction method, which are not suitable for large-scale industrial production. Therefore, it is of great practical significance to develop a simple, low-cost method for preparing a Cu2O-TiO2 nanotube core-sheath structure suitable for industrial production and with highly controllable filling rate. Summary of the invention
[0006] In order to solve the problems mentioned in the background technology, the present invention provides a method for preparing a Cu2O-TiO2 nanotube core-sheath structure. First, a titanium alloy sheet and a stainless steel sheet are used as an anode and a cathode respectively, and then a heat treatment annealing is performed to obtain a titanium alloy sheet with TiO2 nanotubes on the surface;
[0007] Secondly, a titanium alloy sheet with TiO2 nanotubes on the surface, a saturated calomel electrode and a platinum mesh were used as a working electrode, a reference electrode and a counter electrode respectively, and a titanium alloy sheet with TiO2 nanotubes on the surface having a high conductive bottom and a low conductive top was prepared by electrochemical cathode reduction;
[0008] Finally, the titanium alloy sheet of TiO2 nanotubes with different conductivity, saturated calomel electrode and platinum mesh were used as working electrode, reference electrode and counter electrode respectively, and Cu2O was loaded into the interior of the TiO2 nanotube array through electrochemical pulse deposition to form a core-sheath structure.
[0009] In one embodiment, the constant current regulated power supply voltage of the electrochemical anodization is 20V to 35V, and the anodization time is 1h to 2h.
[0010] In one embodiment, the heat treatment annealing method is to place the electrochemically anodized titanium alloy sheet into a muffle furnace, heat it to 400°C~500°C in an air atmosphere, and keep it warm for 1h~3h, and cool it with the furnace to obtain a titanium alloy sheet with TiO2 nanotubes on the surface.
[0011] In one embodiment, the titanium alloy sheet with TiO2 nanotubes on its surface is placed in a second electrolyte solution for ultrasonic vibration for 1 to 3 minutes before being subjected to electrochemical cathode reduction.
[0012] In one embodiment, the voltage of the electrochemical cathode reduction is between -1.5V and -1.8V, and the cathode reduction time is between 1min and 3min.
[0013] In one embodiment, the titanium alloy sheet with TiO2 nanotubes having different conductivity is placed in an electroplating solution for ultrasonic vibration for 1 to 3 minutes before electrochemical pulse deposition.
[0014] In one embodiment, the electrochemical pulse deposition takes -0.6V to -0.8V for 50ms to 100ms, and 0V for 50ms to 100ms as one cycle, and is performed for 4000 cycles, that is, the deposition time is 400s to 800s.
[0015] In one embodiment, the titanium alloy material is any one of TA24 titanium alloy, TA22 titanium alloy, and TC4 titanium alloy.
[0016] In one embodiment, the first electrolyte solution used in the electrochemical anodization is prepared by adding 2.4 g to 4.8 g of NH4F into 40 mL to 80 mL of deionized water to fully dissolve, and then adding 400 mL to 800 mL of ethylene glycol to mix evenly.
[0017] In one embodiment, the second electrolyte solution used in the electrochemical cathode reduction is prepared by adding 132g to 198g of (NH4)2SO4 to 1L of deionized water to prepare a 1mol / L to 1.5mol / L (NH4)2SO4 aqueous solution.
[0018] In one embodiment, the plating solution used in the electrochemical pulse deposition is prepared by fully stirring and mixing 200 mL of a 0.3 mol / L to 0.4 mol / L CuSO4 aqueous solution and 200 mL of a 3 mol / L to 4 mol / L lactic acid solution, adding 138 mL to 152 mL of a 5 mol / L NaOH aqueous solution, and adjusting the pH value to 11 to 12.
[0019] In one embodiment, the method for preparing the Cu2O-TiO2 nanotube core-sheath structure provided by the present invention specifically comprises the following steps:
[0020] S100, electrochemical anodization preparation of TiO2 nanotubes: a titanium alloy sheet and a stainless steel sheet are used as an anode and a cathode respectively and are placed in a first electrolyte solution, a constant current stabilized voltage power supply is used to apply a voltage of 20V to 35V for anodization for 1h to 2h, the sheet is taken out, rinsed and blown dry, and then placed in a muffle furnace and heated to 400°C to 500°C in an air atmosphere and kept warm for 1h to 3h, and then cooled with the furnace to obtain a titanium alloy sheet with TiO2 nanotubes on the surface;
[0021] S200, electrochemical cathode reduction of TiO2 nanotubes: put the titanium alloy sheet with TiO2 nanotubes on the surface into the second electrolyte solution and ultrasonically vibrate for 1min to 3min, then use the titanium alloy sheet, saturated calomel electrode and platinum mesh as working electrode, reference electrode and counter electrode respectively, polarize at -1.5V to -1.8V for 1min to 3min, then take out, wash and dry, to obtain a titanium alloy sheet with TiO2 nanotubes with high conductivity bottom and low conductivity top;
[0022] S300, electrochemical pulse deposition of Cu2O: Put the titanium alloy sheet with TiO2 nanotubes with different conductivity into the electroplating solution and ultrasonically vibrate for 1min to 3min. Use the titanium alloy sheet, saturated calomel electrode and platinum mesh as the working electrode, reference electrode and counter electrode respectively. Use -0.6V to -0.8V 50ms to 100ms, 0V 50ms to 100ms as one cycle. Perform 4000 cycles, that is, the deposition time is 400s to 800s. Take out, wash and blow dry to obtain the Cu2O-TiO2 nanotube core-sheath structure.
[0023] The present invention also provides a Cu2O-TiO2 nanotube core-sheath structure, which is prepared by any of the preparation methods described above.
[0024] The present invention provides a method for preparing a Cu2O-TiO2 nanotube core-sheath structure, which has the following technical principles and effects compared with the prior art:
[0025] 1. The present invention adopts electrochemical anodizing technology and heat treatment annealing to prepare anatase TiO2 nanotube arrays with highly controllable tube diameter and tube length. By adjusting the electrochemical anodizing parameters and heat treatment annealing parameters, the diameter, tube length and crystal form of the TiO2 nanotubes can be highly controlled, which solves the problem of Cu2O filling caused by the disorder of TiO2 nanotubes prepared by hydrothermal method, and is suitable for large-scale production.
[0026] 2. The present invention adopts electrochemical cathode reduction technology to selectively reduce the bottom of the TiO2 nanotube to improve the conductivity, thereby forming electrical characteristics of a high-conductivity bottom and a low-conductivity top. This step is a necessary step to achieve the nucleation and growth of Cu2O from the bottom to the top of the TiO2 nanotube, solving the problem of effectively filling Cu2O into the interior of the TiO2 nanotube.
[0027] 3. The present invention adopts electrochemical pulse deposition technology to solve the problem of Cu 2+ The diffusion and mass transfer problem of Cu2O is blocked, and the defects of low filling rate of Cu2O-TiO2 nanotube composite structure prepared by chemical reduction method, hydrothermal method and template method are overcome. By controlling the electrochemical pulse deposition parameters, the filling rate of Cu2O can be highly controlled.
[0028] 4. This method has the advantages of simple operation equipment, few preparation steps, low preparation cost, low preparation environment requirements, high controllability and suitability for industrial production, and is expected to achieve large-scale production applications. It is also suitable for the preparation of core-sheath structures of other metals or metal oxides loaded on TiO2 nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0030] Figure 1 is a scanning electron microscope image of TiO2 nanotubes after electrochemical anodization;
[0031] Figure 2 is a scanning electron microscope image of TiO2 nanotubes after electrochemical cathode reduction;
[0032] Figure 3A is the Nyquist plot of TiO2 nanotubes after electrochemical cathode reduction;
[0033] Figure 3B is the Bode plot of TiO2 nanotubes after electrochemical cathode reduction;
[0034] Figure 4 is a scanning electron microscope image of the core-sheath structure of Cu2O-TiO2 nanotubes after electrochemical pulse deposition;
[0035] Figure 5 This is the X-ray energy spectrum point scanning diagram of the core-sheath structure of Cu2O-TiO2 nanotubes;
[0036] Figure 6 This is the X-ray diffraction spectrum of the core-sheath structure of Cu2O-TiO2 nanotubes;
[0037] Figure 7 The scanning electron microscopy images of the core-sheath structure of Cu2O-TiO2 nanotubes obtained at different deposition potentials;
[0038] Figure 8 The scanning electron microscopy images of the core-sheath structure of Cu2O-TiO2 nanotubes obtained at different deposition times;
[0039] Fig. 9 Scanning electron microscope images of the core-sheath structure of Cu2O-TiO2 nanotubes obtained with different anode and cathode pulse width ratios. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The present invention provides the following method for preparing a Cu2O-TiO2 nanotube core-sheath structure:
[0042] Example 1
[0043] The specific operations are as follows:
[0044] S100, Preparation of TiO2 Nanotubes by Electrochemical Anodization
[0045] A 30 mm × 20 mm × 2 mm TA24 titanium alloy sheet was polished to 2000#, then ultrasonically cleaned with ethanol and deionized water for 10 min, taken out and blown dry for later use;
[0046] Prepare the first electrolyte solution: dissolve 2.4 g of NH4F in 40 mL of deionized water under stirring, add 400 mL of ethylene glycol, and then stir the electrolyte thoroughly to obtain a stable and transparent first electrolyte solution for standby use;
[0047] Use titanium alloy sheet as anode, stainless steel electrode as cathode, anode-cathode area ratio of 1, electrode spacing of 3cm, oxidize at DC voltage of 30V for 1h, take out, wash and dry, then place in a muffle furnace and heat at a rate of 4℃ / min to 400℃ and keep warm for 2h to obtain highly ordered TiO2 nanotubes.
[0048] Electrochemical cathode reduction of S200 and TiO2 nanotubes
[0049] 132.14 g of (NH4)2SO4 was added to 1 L of deionized water to prepare a 1 mol / L (NH4)2SO4 aqueous solution as the second electrolyte solution, and the titanium alloy sheet obtained in step S100 was placed in the second electrolyte solution for ultrasonic cleaning for 2 min. Then, the titanium alloy sheet obtained in step S100 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the platinum mesh was used as the counter electrode, and cathode reduction was performed at -1.7 V for 60 s.
[0050] Electrochemical pulse deposition of S300 and Cu2O
[0051] 15g of CuSO4·5H2O was added to 200mL of deionized water to prepare a 0.3mol / L CuSO4 aqueous solution, and 75mL of lactic acid was added to 200mL of deionized water to prepare a 3mol / L lactic acid solution. The two solutions were fully mixed to form a copper lactate aqueous solution. 40g of NaOH was added to 200mL of deionized water to prepare a 5mol / L NaOH aqueous solution, and 138mL of NaOH aqueous solution was added to the copper lactate aqueous solution to form an alkaline copper lactate aqueous solution. The pH value was adjusted to 11 and used as an electroplating solution.
[0052] The titanium alloy sheet reduced in step S200 was placed in an electroplating solution for ultrasonic cleaning for 2 minutes. Then, the titanium alloy sheet reduced in step S200 was used as a working electrode, a saturated calomel electrode was used as a reference electrode, and a platinum mesh was used as a counter electrode. The deposition was performed for 400 seconds at pulse parameters of -0.7V 50ms and 0V50ms, i.e., the cathode and anode pulse width ratio was 1, to obtain a Cu2O-TiO2 nanotube core-sheath structure.
[0053] The present invention also provides the following comparative example
[0054] The Cu2O / TNTs heterostructure nanocomposite material prepared in the embodiment disclosed in the patent document with publication number CN103225097A (publication date July 31, 2013).
[0055] The nanotubes prepared in the above embodiment were observed by electron microscope, and the electron microscope scanning diagram shown in the attached figure was obtained. The specific analysis is as follows:
[0056] The highly ordered TiO2 nanotube structure obtained in step S100 of Example 1 is shown in FIG. Figure 1 , where the tube diameter is about 90nm and the tube length is about 1.2μm.
[0057] The microstructure of TiO2 nanotubes after electrochemical cathode reduction is shown in Figure 2 As shown in the figure, it can be seen that the microscopic morphology of TiO2 nanotubes before and after electrochemical cathode reduction has no obvious change, the tube diameter is about 90nm, and the tube length is about 1.2μm. The electrochemical cathode reduction process will not cause damage to the TiO2 nanotubes, and thus will not affect the subsequent electrochemical pulse deposition process of Cu 2+ mass transfer diffusion process.
[0058] The present invention also conducts electrochemical impedance spectroscopy test on the TiO2 nanotubes after electrochemical cathode reduction. The test results are as follows: Figure 3A and Figure 3B As shown, the test interval is 10 -2 Hz~10 5Hz, and the excitation amplitude was 5 mV. Zview2.0 software was used to fit the electrochemical impedance spectroscopy data, and the fitting results are shown in Table 1.
[0059] Table 1
[0060]
[0061] from Figure 3A , Figure 3B As can be seen from Table 1, after electrochemical cathode reduction, the barrier layer resistance of TiO2 nanotubes R bl decreases by one order of magnitude, while the nanotube layer resistance R nt Basically unchanged, thus establishing the electrical characteristics of the high conductivity bottom and low conductivity top.
[0062] The core-sheath structure of the Cu2O-TiO2 nanotubes prepared in step S300 in the embodiment is as follows: Figure 4 As shown. Figure 4 It can be seen that Cu2O completely fills the interior of the TiO2 nanotubes, and the deposition path of Cu2O is from the bottom to the top of the nanotubes.
[0063] Reference Figure 5 According to EDS detection, Cu element appears in the TiO2 nanotubes after electrochemical deposition. After removing the atomic ratio of TiO2, it can be determined that the atomic ratio of Cu and O in the deposit is about 2:1, that is, the deposit is Cu2O.
[0064] Reference Figure 6 It can be seen that the characteristic diffraction peaks with 2θ of 29.61°, 39.76°, 42.69° and 61.82° correspond to the (1 1 0), (1 1 1), (2 0 0) and (2 2 0) crystal planes of Cu2O, respectively. There are no diffraction peaks of Cu and CuO, which can further determine that the deposit is Cu2O, indicating that the Cu2O-TiO2 nanotube core-sheath structure is successfully prepared.
[0065] The comparative example provided by the present invention is to directly place TiO2 nanotubes prepared by electrochemical anodization in an electrolyte containing copper sulfate and lactic acid, and load Cu2O nanoparticles into TiO2 nanotubes by constant potential deposition to prepare Cu2O / TNTs heterojunction nanocomposite materials. Figure 1 , Figure 2As can be clearly seen from Figure 3, the Cu2O is only loaded on the surface and the mouth of the TiO2 nanotubes, and is not filled into the interior of the TiO2 nanotubes to achieve a highly controllable filling rate. In the present invention, the bottom of the TiO2 nanotubes is selectively reduced by an electrochemical cathode reduction method to obtain a TiO2 nanotube with a high conductivity bottom and a low conductivity top, so that the Cu2O nucleation growth path during the electrochemical pulse deposition process is along the bottom to the top of the TiO2, and the Cu2O loading amount is highly controllable by adjusting the electrochemical pulse deposition parameters.
[0066] To further demonstrate that the preparation method provided by the present invention can achieve a high degree of controllability of the filling effect of Cu2O by controlling the electrochemical pulse deposition parameters, the present invention also provides the following embodiments:
[0067] The difference between the preparation method in the embodiment shown in Table 2 and that in embodiment 1 is only the difference in deposition potential:
[0068] Table 2
[0069]
[0070] The difference between the preparation method in the embodiment shown in Table 3 and that in embodiment 1 is only the deposition time:
[0071] Table 3
[0072]
[0073] The difference between the preparation method in the embodiment shown in Table 4 and that in Embodiment 1 is only the difference in the anode-cathode pulse width ratio:
[0074] Table 4
[0075]
[0076] It should be noted that the actual process parameters of the above-mentioned Examples 4, 7 and 10 are the same as those of Example 1, so they can be regarded as repeatable tests of Example 1.
[0077] The nanotubes prepared in the above embodiment were observed by electron microscope, and the following Figures 7 to 9 The electron microscope scanning diagram shown, wherein Example 2, Example 3, Example 4 and Example 5 correspond to Figure 7 (a), (b), (c) and (d); Example 6, Example 7 and Example 8 correspond to Figure 8 (a), (b) and (c); Example 9, Example 10 and Example 11 correspond to Fig. 9 (a), (b) and (c) in the figure.
[0078] from Figure 7It can be seen that by controlling the electrochemical pulse deposition potential, Cu2O can be nucleated at the bottom of the TiO2 nanotube and grow from the bottom to the top of the TiO2 nanotube, thus forming a core-sheath structure. Figure 8 and Fig. 9 It can be seen that by controlling the electrochemical pulse deposition time and the anode-cathode pulse width ratio, the filling amount of Cu2O inside the TiO2 nanotube can be further controlled. It can be seen that by using the preparation method of the Cu2O-TiO2 nanotube core-sheath structure provided by the present invention, the filling rate of Cu2O can be highly controlled by controlling the electrochemical pulse deposition parameters.
[0079] Although the terms such as electrolyte solution, electroplating solution, electrochemical anodic oxidation, electrochemical cathode reduction, etc. are used more frequently in this article, the possibility of using other terms is not excluded. These terms are used only to more conveniently describe and explain the essence of the present invention; interpreting them as any additional limitation is contrary to the spirit of the present invention.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a Cu2O-TiO2 nanotube core-sheath structure, characterized in that: Firstly, a titanium alloy sheet and a stainless steel sheet are used as an anode and a cathode respectively, and then subjected to electrochemical anodization and heat treatment annealing to obtain a titanium alloy sheet with TiO2 nanotubes on the surface; Secondly, a titanium alloy sheet with TiO2 nanotubes on the surface, a saturated calomel electrode and a platinum mesh are used as a working electrode, a reference electrode and a counter electrode respectively to prepare a titanium alloy sheet with TiO2 nanotubes on the surface having a high conductive bottom and a low conductive top through electrochemical cathode reduction, wherein the voltage of the electrochemical cathode reduction is -1.5V to -1.8V and the cathode reduction time is 1min to 3min; Finally, the titanium alloy sheet of TiO2 nanotubes with different conductivity, saturated calomel electrode and platinum mesh were used as working electrode, reference electrode and counter electrode respectively, and Cu2O was loaded into the interior of TiO2 nanotube arrays through electrochemical pulse deposition to form a core-sheath structure. The electrochemical pulse deposition takes -0.6V to -0.8V for 50ms to 100ms, and 0V for 50ms to 100ms as one cycle, and is carried out for 4000 cycles, that is, the deposition time is 400s to 800s.
2. The method for preparing the Cu2O-TiO2 nanotube core-sheath structure according to claim 1, characterized in that: The constant current regulated power supply voltage of the electrochemical anodic oxidation is 20V to 35V, and the anodic oxidation time is 1h to 2h.
3. The method for preparing the Cu2O-TiO2 nanotube core-sheath structure according to claim 1, characterized in that: The heat treatment annealing method is to place the electrochemically anodized titanium alloy sheet into a muffle furnace, heat it to 400°C to 500°C in an air atmosphere, keep it warm for 1h to 3h, and cool it in the furnace to obtain a titanium alloy sheet with TiO2 nanotubes on the surface.
4. The method for preparing the Cu2O-TiO2 nanotube core-sheath structure according to claim 1, characterized in that: The titanium alloy sheet is any one of TA24 titanium alloy, TA22 titanium alloy and TC4 titanium alloy.
5. The method for preparing the Cu2O-TiO2 nanotube core-sheath structure according to claim 1, characterized in that: The first electrolyte solution used in the electrochemical anodization is prepared by adding 2.4 g to 4.8 g of NH4F into 40 mL to 80 mL of deionized water to fully dissolve, and then adding 400 mL to 800 mL of ethylene glycol to mix evenly.
6. The method for preparing the Cu2O-TiO2 nanotube core-sheath structure according to claim 1, characterized in that: The second electrolyte solution used in the electrochemical cathode reduction is prepared by adding 132g to 198g of (NH4)2SO4 to 1L of deionized water to prepare a 1mol / L to 1.5mol / L (NH4)2SO4 aqueous solution.
7. The method for preparing the Cu2O-TiO2 nanotube core-sheath structure according to claim 1, characterized in that: The electroplating solution used in the electrochemical pulse deposition is prepared by fully stirring and mixing 200 mL of a 0.3 mol / L to 0.4 mol / L CuSO4 aqueous solution and 200 mL of a 3 mol / L to 4 mol / L lactic acid solution, adding 138 mL to 152 mL of a 5 mol / L NaOH aqueous solution, and adjusting the pH value to 11 to 12.
8. A Cu2O-TiO2 nanotube core-sheath structure, characterized in that: The Cu2O-TiO2 nanotube core-sheath structure is prepared by the preparation method of any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation of Cu2O / TNTs (TiO2 nanotubes) heterojunction nano composite material and CO2 photoreduction method
CN103225097A
Method for sensitizing TiO2 nanotube array photoelectrode through Cu2O nano particles
CN105040062A
TiO2-based nanometer heterojunction composite photocatalytic material and preparation method thereof
CN106582641A
Preparing method for Cu2O nano particle / TiO2 nano tube array composite heterojunction film
CN108179455A
Research method for preparation of novel high-catalytic activity electrode and electro-catalytic degradation of methyl blue thereof
CN106277228A